Influence of preform interlacement on the low velocity impact behavior of multilayer textile composites - Fangueiro, Raúl (2010)
Impact property of composite material is influenced not only by the type of fiber/matrix, but also by the woven structure of the reinforcement. Presence of 3D fibers in reinforcement is reported to enhance the performance of textile composites in an impact event. This article attempts to study the influence of interlacements in the multilayer woven interlocked 3D structures on the impact properties of the composite material reinforced with them. Low velocity impact testing was carried out on an instrumented drop weight impact tester to obtain loadelongation- time plots of the impact event. It has been observed that increased interlacement in the structure improves the impact resistance of the multilayer textile composites. Further, damage area maps have been developed to understand and analyze the interlacement effect on the impact behavior.